IMPLEMENTASI PROGRAM GAPAJAK SEBAGAI UPAYA PELESTARIAN CERITA RAKYAT JAMBI DALAM MENINGKATKAN LITERASI BUDAYA PESERTA DIDIK - Mayang Ismaya; Endah Yunita; Fajarli; Hamidah Rosifa Sikumbang; Eka Sastrawati; Destrinelli; Indryani; Muhammad Sofwan; Ahmad Syarif; Atri Widowati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Jambi Province possesses rich cultural heritage in the form of folklore, legends, and fairy tales that embody local wisdom values. However, in the era of globalization and digitalization, the existence of folklore has increasingly been marginalized and is less familiar to younger generations. This study aims to describe and analyze the implementation of the GAPAJAK Flagship Program (Gerakan Pelestarian Cerita Rakyat Jambi untuk Anak / Jambi Folklore Preservation Movement for Children) as an effort to preserve local culture while strengthening students’ character education and literacy. This research employed a qualitative method with a case study approach conducted at MTs Muhammadiyah Kota Jambi. Data were collected through observation, interviews with teachers and students, and documentation of activities and students’ works. The GAPAJAK program was implemented using a Project-Based Learning approach that integrated Indonesian language learning with activities of reading, writing, and developing folklore based on Jambi local wisdom. The findings indicate that the GAPAJAK program enhances students’ literacy skills, creativity, and critical thinking, fosters pride in local culture, and strengthens character values such as honesty, cooperation, and environmental awareness. In addition, the program reinforces teachers’ roles as facilitators of creative learning and improves the school’s image as an institution committed to cultural preservation. Therefore, the GAPAJAK program can serve as an innovative model for integrating local culture into school learning as a sustainable effort to preserve Jambi folklore.